2005
DOI: 10.1007/s10593-005-0299-9
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 2,3-Dioxopyrrolo[2,1-a]isoquinolines with Active N-Nucleophiles

Abstract: It is shown that 2,3-dioxopyrrolo [2,1-a]isoquinolines react readily with aliphatic diamines and hydroxyamine with opening of the dioxopyrrole ring and formation of the corresponding bisenaminoketoamides and hydroxamic acids. Reaction with the thiosemicarbazide and hydrazides of aromatic acids proceeds without opening of the pyrrole ring at the ketone carbonyl. Derivatives of hexahydropyridazine are formed when compounds with carboxyethyl groups at position 1 react with hydrazine.It has been shown previously t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The investigations showed that on boiling dioxopyrroline 1a with the hydrazides of cyanoacetic and p-aminobenzoic acids reaction proceeds according to the previously known scheme with the formation of the corresponding hydrazones 6 and 7, i.e. without opening of the pyrroledione ring [5].…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The investigations showed that on boiling dioxopyrroline 1a with the hydrazides of cyanoacetic and p-aminobenzoic acids reaction proceeds according to the previously known scheme with the formation of the corresponding hydrazones 6 and 7, i.e. without opening of the pyrroledione ring [5].…”
mentioning
confidence: 94%
“…On interacting ester 2a with other hydrazides, such as cyanoacetylhydrazide and benzoic acid hydrazide in boiling glacial acetic acid or 2-propanol, no new products were isolated, which may be explained by the weak nucleophilic properties of the reactants used. It is known that 2,3-dioxopyrrolo[2,1-a]isoquinolines frequently play the role of acylating reagents, interacting with N-nucleophiles with opening of the pyrrole ring [4][5][6][7]. It therefore seemed of interest to study the acylation reaction of hydrazides with these reagents with the aim of obtaining substances analogous to compounds 5a,b in structure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H NMR spectra were taken on a Bruker-300 spectrometer at 300 MHz with HMDS as the internal standard (δ 0.05 ppm). The assignment of the singlet of the vinyl proton in the enamino ketone fragment is based on extensive data, for example, the results of our previous work [2]. The position of the singlet of the vinyl proton of the anthrone side chain corresponded to the calculated value [3].…”
mentioning
confidence: 99%